2012
DOI: 10.1517/14740338.2012.698608
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of eribulin mesylate: a new therapeutic option in the treatment of metastatic breast cancer

Abstract: Phase II and a recent Phase III trial indicate that eribulin is well tolerated with a predictable safety profile. The most frequent adverse events observed in patients receiving eribulin were asthenia/fatigue, neutropenia, alopecia, peripheral neuropathy and nausea. It represents a new treatment option in the setting of anthracycline and taxane-refractory metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The most common adverse effects observed in both the treatment arms were asthenia (or fatigue) and neutropenia, most of which were Grade 1 or 2. [44,45] Grade 3 or 4 events that were more frequent in the eribulin group than in the TPC group were leukopenia, neutropenia, and peripheral neuropathy. There was more myelosuppression with eribulin, incidence of Grade 3 or 4 neutropenia being 45% versus 21%; majority of these were asymptomatic.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…The most common adverse effects observed in both the treatment arms were asthenia (or fatigue) and neutropenia, most of which were Grade 1 or 2. [44,45] Grade 3 or 4 events that were more frequent in the eribulin group than in the TPC group were leukopenia, neutropenia, and peripheral neuropathy. There was more myelosuppression with eribulin, incidence of Grade 3 or 4 neutropenia being 45% versus 21%; majority of these were asymptomatic.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Recently, various agents including antitubulins (eg, vinorelbine, 5 , 6 ixabepilone, 7 and eribulin 8 ), antimetabolites (eg, capecitabine 9 , 10 and gemcitabine 11 , 12 ), topoisomerase I inhibitors (eg, irinotecan 13 ), and platinum analogs (eg, cisplatin 14 ) have been evaluated for their efficacy and safety in this setting when used either alone or in combination with other cytotoxic agents. Compared with single agent, some studies found that doublet agents could gain additional clinical benefits including progression-free survival (PFS), overall survival (OS), and overall response rate (ORR), 7 , 11 which could offer an option for women with anthracycline-and taxane-pretreated MBC.…”
Section: Introductionmentioning
confidence: 99%